Indo-Pacific Humpback Dolphins in Borneo: A Review of Current Knowledge with Emphasis on Sarawak - Minton, Gianna; Zulkifli Poh, A.N.; Peter, C.; Porter, L.; Kreb, D. (Elsevier B.V., 2016)
Indo-Pacific humpback dolphins (Sousa chinensis) are documented from various locations along Borneo's coast, including three sites in Sarawak, Malaysia, three sites in Sabah, Malaysia, three locations in Kalimantan, Indonesia and the limited coastal waters of the Sultanate of Brunei. Observations in all these areas indicate a similar external morphology, which seems to fall somewhere between that documented for Chinese populations known as S. chinensis, and that of Sousa sahulensis in Australia and Papua New Guinea. Sightings occur in shallow nearshore waters, often near estuaries and river mouths, and associations with Irrawaddy dolphins (Orcaella brevirostris) are frequently documented. Population estimates exist for only two locations and sightings information throughout Borneo indicates that frequency of occurrence is rare and group size is usually small. Threats from fisheries by-catch and coastal development are present in many locations and there are concerns over the ability of these small and fragmented populations to survive. The conservation and taxonomic status of humpback dolphins in Borneo remain unclear, and there are intriguing questions as to where these populations fit in our evolving understanding of the taxonomy of the genus.